Investigation of different Damask rose (Rosa damascena Mill.) oil samples from traditional markets in Fars (Iran); focusing on the extraction method - Mahmoodreza Moein; Hamed Etemadfard; Mohammad M. Zarshenas (Shiraz University of Medical Sciences, 2016)
Bearing essential oil, Damask rose (Rosa damascena Mill.) is widely applied in pharmaceutical and perfumery industries. In Iran, the oil and hydrosol are obtained in two famous centers, Kashan and Fars. The process can be performed either traditionally or conventionally. Moreover, rose oil samples are produced synthetically by commercial industries. Current work outlines the differences between collected samples. Eight samples yielded from those present methods were collected and analyzed using a gas chromatograph connected to a mass detector. Samples were prepared traditionally, conventionally or synthetically. Results revealed that phenyl ethyl alcohol, β-citronellol and phenethyl acetate were the most detected component in synthetic sample (38.77, 15.73% and 15.29%, respectively). The synthetic sample involved two more major constituents (9.52 and 2.86%). Traditionally and conventionally produced samples mainly contained hydrocarbons as nonadecane (17.42 - 40.38%), heneicosane (17.26 - 26.17%), 1-nonadecene (4.98 - 15.33%), heptadecane (3.96 - 10.33%) and eicosane (2.83 - 5.19%), but lower in total rose alcohol from 0.00% in concentrated traditional samples to 30.24% in the sample prepared by a conventional method. High amounts of hydrocarbons in samples might be related to prolonged and repeated distillation, and thus nearly total amount of rose alcohol is transferred into the water phase.